Digital privacy PRIME - privacy and identity management for Europe - Camenisch, Jan.; Leenes, Ronald; Sommer, Dieter; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book documents the R&D outcome of the PRIME Project, an R&D project partially funded by the European Union's Sixth Framework Programme and the Swiss Federal Office for Education and Science. PRIME has focused on privacy-enhancing identity management techniques and systems to support users? sovereignty over their personal privacy and enterprises? privacy-compliant data processing. During the course of four years, the project has involved over a hundred researchers and professionals from 22 major European academic and industrial organizations conducting R&D work in areas relevant to digital privacy. The book presents 28 detailed chapters organized in five parts: Introductory summary; Legal, social, and economic aspects; Realization of privacy-enhancing user-centric identity management; Exploitation of PRIME results for applications; Conclusions drawn and an outlook on future work As the first coherent presentation of the topic, this book will serve as a valuable source of reference and inspiration for anybody working on digital privacy.
Part I Privacy and Identity Management; An Introduction to Privacy-Enhancing Identity Management; Part II Setting the Stage; The Identity Landscape; The Need for Privacy-Enhancing Identity Management; Regulating Identity Management; User-Centric Privacy-Enhancing Identity Management; Privacy-Enhancing Identity Management in Business; Part III What Technology Can Do for Privacy and How; Introduction: Privacy, Trust, and Identity Management; Architecture; Pseudonyms and Private Credentials; Privacy Models and Languages: Access Control and Data; Privacy Models and Languages: Obligation Policies; Privacy Models and Languages: Assurance Checking; Privacy-Aware Access Control System; Privacy-Aware Identity Lifecycle Management; Privacy Assurance Checking; Security/Trustworthiness Assessment of Platforms; Further Privacy Mechanisms; Reputation Management; Human-Computer Interaction; Technology Assurance; Multilateral Interactions; Part IV PRIME Applied; Collaborative E-Learning; Location-Based Services; e-Health; Airport Security Controls; Privacy and Identity Management Requirements; Part V Conclusion and Outlook.
Electronic reproduction.
Keywords: Internet -- Security measures; Computer security; Data protection; Electronic books